2017
DOI: 10.3390/tropicalmed2040061
|View full text |Cite
|
Sign up to set email alerts
|

Biosocial Determinants of Persistent Schistosomiasis among Schoolchildren in Tanzania despite Repeated Treatment

Abstract: Schistosomiasis is a parasitic disease endemic to Tanzania and other countries of the global south, which is currently being addressed through preventive chemotherapy campaigns. However, there is growing recognition that chemotherapy strategies will need to be supplemented to sustainably control and eventually eliminate the disease. There remains a need to understand the factors contributing to continued transmission in order to ensure the effective configuration and implementation of supplemented programs. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 118 publications
(145 reference statements)
2
20
0
Order By: Relevance
“…In total, 16 (48%) studies assessed childhood health and childhood infectious diseases, mainly centering on under-five mortality (15%), schistosomiasis/intestinal parasites (18%), and childstunting (12%). Concretely, studies showed that maternal, or household access to clean water significantly reduced the risk of under-five mortality (Ahmed et al, 2016;Acheampong et al, 2017Acheampong et al, , 2018, child stunting (Akombi et al, 2017;Vos et al, 2017;Marinda et al, 2018), schistosomiasis (Atalabi et al, 2016;Donohue et al, 2017), and hookworm infections (Baker et al, 2018). Household piped water was one of the three stability factors needed to reduce HIV transmission for newborn infants (Doherty et al, 2007).…”
Section: Poor Access To Wash Resources Disproportionately Impacts Heamentioning
confidence: 99%
See 4 more Smart Citations
“…In total, 16 (48%) studies assessed childhood health and childhood infectious diseases, mainly centering on under-five mortality (15%), schistosomiasis/intestinal parasites (18%), and childstunting (12%). Concretely, studies showed that maternal, or household access to clean water significantly reduced the risk of under-five mortality (Ahmed et al, 2016;Acheampong et al, 2017Acheampong et al, , 2018, child stunting (Akombi et al, 2017;Vos et al, 2017;Marinda et al, 2018), schistosomiasis (Atalabi et al, 2016;Donohue et al, 2017), and hookworm infections (Baker et al, 2018). Household piped water was one of the three stability factors needed to reduce HIV transmission for newborn infants (Doherty et al, 2007).…”
Section: Poor Access To Wash Resources Disproportionately Impacts Heamentioning
confidence: 99%
“…Outside of the home, exposure to open water near schools increases the risk of schistosomiasis (Kapito-Tembo et al, 2009). Other aspects of WASH, including improved sanitation and handwashing, likewise reduced underfive mortality (Ahmed et al, 2016;Dendup et al, 2018), and schistosomiasis (Donohue et al, 2017), or acquiring other soiltransmitted helminths and parasites (Baker et al, 2018). In addition to the availability of sustainable WASH resources, maternal factors contributed to health burdens.…”
Section: Poor Access To Wash Resources Disproportionately Impacts Heamentioning
confidence: 99%
See 3 more Smart Citations